Synthesis and solvent effects on the electronic absorption and fluorescence spectral properties of substituted zinc phthalocyanines - Durmuş, Mahmut; Nyokong, Tebello (Pergamon-Elsevier Science Ltd, 2007)
The synthesis and spectroscopic properties of the following tetra- and octa-substituted aryloxy zinc(Il) phthalocyanines are reported for the first time: 1,(4)-(tetrabenzyloxyphenoxyphthalocyaninato) zinc(II) (7); 2,(3)-(tetrabenzyloxyphenoxyphthalocyaninato) zinc(II) (8); 2,3-(octabenzyloxyphenoxyphthalocyaninato) zinc(Il) (9). The new compounds have been characterized by elemental analysis, IR, 1H NMR spectroscopy and electronic spectroscopy. Spectroscopic properties of these compounds were investigated in different solvents. Protonation of non-peripherally substituted complex 7 resulted in the splitting and red-shifting of the Q-band. The peripherally substituted derivatives 8 and 9, did not show the split in the Q-band. Fluorescence spectra of the derivatives show Stokes shifts typical of MPc complexes. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; zinc; fluorescence; aggregation; solvent effect